Implementasi Model Pembelajaran Problem Based Learning Berbantukan Geogebra untuk Meningkatkan Hasil dan Minat Belajar Siswa: IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUKAN GEOGEBRA UNTUK MENINGKATKAN MINAT BELAJAR SISWA - Musa’ad, Faida; Musa’ad, Faija; Setyo, Arie Anang; Sundari, Sundari; Trisnawati, Nika Fetria (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2023)
This study aims to increase students' interest in learning by using a problem-based learning model and assisted by the GeoGebra application. This type of research is pre-experimental. The research sample was taken from class VIII students of junior high school. Based on the research results, it was found that 72.2% of students were in the upper middle category and the average student response to the use of the Geogebra-assisted PBL learning model reached an average of 3.46 and the average result of learning implementation was 3.71 with a positive category. The results of the N-gain analysis show that the statistical value is respectively 0.865 with a ''P Value (sig)'' of 0.278 because the ''P Value (sig)'' is more than 0.05 indicating that the N-gain value comes from the normal population and the results of hypothesis testing where the t-value is 8,517 with a P-value <0.30 (sig.2-tailed)) 0.00 so that it can be stated that the P-value is smaller than the significance level, which is 0.30 so that H0 is rejected and H1 is accepted. Thus experiments using the problem-based learning model with the help of Geogebra are effectively applied